Selecting the best habitat mapping technique: a comparative assessment for fisheries management in Exmouth Gulf - Scott N. Evans; Scott N. Evans; Nick Konzewitsch; Renae K. Hovey; Gary A. Kendrick; Lynda M. Bellchambers (Frontiers in Marine Science)
A spatially explicit understanding of marine benthic habitats is essential for sustainable marine resource management. While advances in remote sensing, acoustic methodologies, geostatistical modelling, and predictive species distribution models have improved our ability to map underwater habitats, selecting the most appropriate approach, particularly in turbid or remote regions, remains challenging. This study was conducted in the protected nursery area of the Exmouth Gulf Prawn Managed Fishery in Western Australia and compared four commonly used “off-the-shelf” mapping techniques. These included satellite remote sensing, acoustic sounding, predictive modelling, and geostatistical interpolation, with each technique evaluated using comprehensive ground-truthing and output confidence matrices. Geostatistical kriging emerged as the most robust method, delivering the highest predictive accuracy, quantifiable confidence, and spatially explicit seasonal habitat maps. These maps delineated submerged aquatic vegetation, including seagrass and macroalgae, at broad spatial scales and captured seasonal shifts in habitat distribution and density. Our findings enhance knowledge of benthic habitats in Exmouth Gulf and underscore that effective marine habitat mapping, particularly in dynamic and turbid environments, cannot rely on remote methods alone. Spatially balanced field data collection at ecologically relevant temporal scales is essential to support sustainable marine resource management.